Optimalisasi handover dengan teknik komunikasi SBAR di Puskesmas Rawat Inap Kemiling, Kota Bandar Lampung - Pratiwi, Liza Ayu; Triyoso, Triyoso; Kusumaningsih, Dewi (Indonesian Public Health-Observer Information Forum (IPHORR) Kerja sama dengan: Unit Penelitian dan Pengabdian Kep Akademi Keperawatan Baitul Hikmah, 2024)
Background: Handover during shift changes is a very important part of nursing services in transferring information and ensuring continuity of patient care plans. Based on a study conducted in November 2023 at the Kemiling Health Center, it was found that the handover problem was not optimal, which was indicated by the handover being carried out but not in front of the patient and the absence of documentation. Purpose: To apply the handover process using the SBAR communication technique in the KIA Room of the Kemiling Inpatient Health Center UPT, Bandar Lampung City. Method: This type of descriptive research uses a case study approach method. The subjects in the report of the head of the room, and the implementing nurse in the KIA Room of the Kemiling Inpatient Health Center UPT, Bandar Lampung City were 4 people. A meeting was first held on November 21, 2023 to determine the time of intervention as an alternative to solving the problem of nursing overran, namely dissemination of knowledge and role play. The implementation of the dissemination of nursing knowledge using the SBAR technique was carried out on November 22, 2023. Results: The dissemination of knowledge that has been carried out was attended by nurses in the KIA Room and nursing professional students. From the results of the observation, it can be seen that the nurses were enthusiastic in participating in the dissemination of knowledge, all nurses attended the event from start to finish. The implementation of role play has also been carried out by students, and from the results of the observation, nursing overran with the SBAR technique has been carried out optimally and will be even better if carried out in accordance with the theory that has been described in the previous discussion. In its implementation, it has also gone through a process starting from the preparation stage to the implementation stage. Conclusion: The application of the SBAR technique (Situation, Background, Assessment, Recommendation) can be an alternative problem solving in creating a structured communication framework that can be used during patient handove Keywords: Handover; Patient handling; SBAR technique Pendahuluan: Handover selama pergantian shift merupakan bagian yang sangat penting dalam pelayanan keperawatan dalam mentransfer informasi dan menjamin kesinambungan rencana perawatan pasien. Berdasarkan pengkajian yang dilakukan pada Bulan November 2023 di Puskesmas Kemiling, diperoleh masalah bahwa belum optimalnya permasalahan handover yang ditandai dengan handover dilakukan tetapi tidak dilakukan didepan pasien dan tidak adanya pendokumentasian. Tujuan: Untuk mengaplikasikan proses handover menggunakan teknik komunikasi SBAR di Ruang KIA UPT Puskesmas Rawat Inap Kemiling Kota Bandar Lampung. Metode: Jenis penelitian deskriptif dengan menggunakan metode pendekatan studi kasus. Subjek pada laporan kepala ruangan, dan perawat pelaksana di Ruang KIA UPT Puskesmas Rawat Inap Kemiling Kota Bandar Lampung sebanyak 4 orang. Terlebih dahulu dilakukan pertemuan pada tanggal 21 November 2023 untuk menentukan waktu intervensi sebagai alternatif pemecahan masalah tentang overran keperawatan yaitu desiminasi ilmu dan role play. Pelaksanaan kegiatan desiminasi ilmu overran keperawatan dengan teknik SBAR dilaksanakan pada tanggal 22 November 2023. Hasil: Desiminasi ilmu yang telah dilakukan dihadiri oleh perawat-perawat di Ruangan KIA dan mahasiswa profesi ners. Dari hasil observasi terlihat perawat-perawat antusias dalam mengikuti desiminasi ilmu, semua perawat mengikuti acara dari awal sampai akhir. Pelaksanaan role play juga sudah dilakukan oleh mahasiswa, dan dari hasil observasi overran keperawatan dengan teknik SBAR sudah dilakukan secara optimal dan akan semakin baik lagi jika dilakukan sesuai dengan teori yang telah dijabarkan pada pembahasan sebelumnya. Dalam pelaksanaannya pun sudah melalui proses yang dimulai dari tahap persiapan hingga tahap pelaksanaan. Simpulan: Penerapan teknik SBAR (Situation, Background, Assessment, Recommendation) dapat menjadi alternatif pemecahan masalah dalam membuat kerangka komunikasi terstruktur yang dapat digunakan saat serah terima pasien atau handover.